2011
DOI: 10.1002/abc.20064
|View full text |Cite
|
Sign up to set email alerts
|

Peer Involvement Advisors Improve First-Year Student Engagement and Retention

Abstract: Adam Peck describes the Peer Involvement Advising Program at Stephen F. Austin State University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 1 publication
1
7
0
1
Order By: Relevance
“…Some of the reported advantages of mentoring from the mentors' perspective include the positive feelings resulting from acts of altruism, a greater sense of awareness, the opportunity to network and increased appreciation for diversity. This is corroborated by Peck (2011), who found that a strong sense of connection to others, personal development and increased appreciation for diversity are reported as gains by mentors. In their study on an institution-wide peer mentoring programme, Beltman and Schaeben (2012) suggest that benefits for mentors can be summarised as falling within four categories, namely altruistic benefits (characterised by fulfilment from the joy of serving others), cognitive benefits (for example, communication and social skills), social benefits (characterised by the formation of new networks and friendships) and lastly personal growth (characterised by empathy and a sense of duty).…”
Section: Benefits Of Mentoring For the Mentorsupporting
confidence: 55%
“…Some of the reported advantages of mentoring from the mentors' perspective include the positive feelings resulting from acts of altruism, a greater sense of awareness, the opportunity to network and increased appreciation for diversity. This is corroborated by Peck (2011), who found that a strong sense of connection to others, personal development and increased appreciation for diversity are reported as gains by mentors. In their study on an institution-wide peer mentoring programme, Beltman and Schaeben (2012) suggest that benefits for mentors can be summarised as falling within four categories, namely altruistic benefits (characterised by fulfilment from the joy of serving others), cognitive benefits (for example, communication and social skills), social benefits (characterised by the formation of new networks and friendships) and lastly personal growth (characterised by empathy and a sense of duty).…”
Section: Benefits Of Mentoring For the Mentorsupporting
confidence: 55%
“…Additional research highlights the expanded interpersonal skills, increased maturity, a sense of responsibility, communication skills, and other qualities including patience and compassion developed by peer mentors (Budge, 2006;McLean, 2004). Furthermore, Peck (2011) suggested that paid peer mentors in a peer advising program were more likely to seek leadership experiences, had increased appreciation for diversity, enhanced listening skills, and a stronger sense of connection between personal and learning development (p. 25). However, the focus of Peck's (2011) article was again on the program and mentees, with benefits to the peer mentors only briefly mentioned.…”
Section: Peer Mentor Experiencementioning
confidence: 99%
“…Furthermore, Peck (2011) suggested that paid peer mentors in a peer advising program were more likely to seek leadership experiences, had increased appreciation for diversity, enhanced listening skills, and a stronger sense of connection between personal and learning development (p. 25). However, the focus of Peck's (2011) article was again on the program and mentees, with benefits to the peer mentors only briefly mentioned. We turn our attention to two studies that have begun to document the benefits experienced by mentors.…”
Section: Peer Mentor Experiencementioning
confidence: 99%
“…First-year seminars can facilitate forms of applied learning and enable students to apply skills to their future coursework (Karp et al, 2017). Peer education has the potential to enhance undergraduate student learning development, and retention (Peck, 2011). Capstone experiences are ideally designed to facilitate students’ ability to demonstrate critical thinking, communication skills, problem-solving, and team building (Young et al, 2017).…”
Section: Review Of Literaturementioning
confidence: 99%